Predictors of Spontaneous Rupture of Hepatocellular Carcinoma and Clinical Outcomes Following Hepatectomy - Chen, Yiran; Guo, Deliang; Li, Xinyi; Xu, Chang; Zhu, Qian (Frontiers in Oncology, 2022)
Objective To explore the independent predictive factors of spontaneous tumor rupture (STR) in patients undergoing curative resection of hepatocellular carcinoma (HCC), and to evaluate the impact of STRHCC on long-term survival after hepatectomy. Methods The clinicopathological parameters of 106 patients with STRHCC and 201 patients with non-ruptured HCC who underwent hepatectomy from January 2007 to November 2011 at the Eastern Hepatobiliary Surgery Hospital and Zhongnan Hospital of Wuhan University were analyzed using propensity score matching (PSM) and a logistic regression model. Results Factors including hypertension, cirrhosis, total bilirubin (TB), tumor size, and ascites were independent predictors of STR. For all 307 HCC patients, the 1-, 3- and 5-year overall survival (OS) rates were 54.0%, 37.3% and 33.8%, respectively. After PSM, the 1-, 3-, and 5-year OS rates in the ruptured group remained significantly lower at 41.5%, 23.5%, and 17.5% when compared with the non-ruptured group at 70.8%, 47.1%, and 37.6%, respectively, while the 1-, 3-, and 5-year disease-free survival (DFS) rates between the groups did not differ significantly (50.4%, 35.1%, 27.1% vs 55.4%, 38.2%, 27.4%). STRHCC was significantly associated with increased risk of OS, but not of shorter DFS. No significant difference in postoperative morbidity or hospital death was observed between the groups. Conclusion Factors including hypertension, liver cirrhosis, higher TB levels, tumor size > 5cm, and ascites are significant predictors of STR. The recurrence rate of patients in the ruptured group was significantly higher than that of patients in the non-ruptured group. STR results in poorer OS but not DFS in patients undergoing curative resection for HCC. STRHCC has no impact on postoperative morbidity and mortality after hepatectomy.